2020
DOI: 10.3389/fonc.2020.01661
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-33b Suppresses Epithelial–Mesenchymal Transition Repressing the MYC–EZH2 Pathway in HER2+ Breast Carcinoma

Abstract: Downregulation of miR-33b has been documented in many types of cancers and is being involved in proliferation, migration, and epithelial-mesenchymal transition (EMT). Furthermore, the enhancer of zeste homolog 2-gene (EZH2) is a master regulator of controlling the stem cell differentiation and the cell proliferation processes. We aim to evaluate the implication of miR-33b in the EMT pathway in HER2+ breast cancer (BC) and to analyze the role of EZH2 in this process as well as the interaction between them. miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Our experiment showed that E-cadherin and Vimentin were increased while N-cadherin diminished in TU177 and Tu686 cells as a response to EZH2 downregulation, indicating that EZH2 downregulation inhibited the EMT of LGC. In consistence with our results, silencing EZH2 also repels the EMT in esophageal, lung, ovarian, and breast cancers [10,[25][26][27]. Taken together, we demonstrated that EZH2 downregulation inhibits the EMT of LGC cells.…”
Section: Discussionsupporting
confidence: 90%
“…Our experiment showed that E-cadherin and Vimentin were increased while N-cadherin diminished in TU177 and Tu686 cells as a response to EZH2 downregulation, indicating that EZH2 downregulation inhibited the EMT of LGC. In consistence with our results, silencing EZH2 also repels the EMT in esophageal, lung, ovarian, and breast cancers [10,[25][26][27]. Taken together, we demonstrated that EZH2 downregulation inhibits the EMT of LGC cells.…”
Section: Discussionsupporting
confidence: 90%
“…Aberrant expressions of various miRNAs have been identified in different tumors, including colorectal cancer, gastric cancer, breast cancer, and NSCLC. [10][11][12][13] It has been well documented that miRNA can affect the invasion and metastasis of cancer through EMT. 14 In previous studies, we screened the miRNAs with low expression in LUAD through the TCGA database and verified in tissues and cells.…”
Section: Introductionmentioning
confidence: 99%
“…We predicted the candidate miRNAs targeting c-Myc via ENCORI (The Encyclopedia of RNA Interactomes) database. miR-33b-5p, a tumor suppressor gene, which directly inhibits c-Myc in several cancers, was selected for validation [ 27 30 ]. Indeed, silenced FLOT2 upregulated the miR-33b-5p level in 5-8F cells, while FLOT2 overexpression downregulated miR-33b-5p expression in 6-10B cells ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%